Endoscopic-assisted transorbital surgery: Where do we stand on the scott’s parabola? personal considerations after a 10-year experience - Dallan, Iacopo; Cristofani-Mencacci, Lodovica; Fiacchini, Giacomo; Turri-Zanoni, Mario; van Furth, Wouter; de Notaris, Matteo; Picariello, Miriana; Alexandre, Enrico; Georgalas, Christos; Bruschini, Luca (Frontiers in Oncology, 2022)
Transorbital approaches are genuinely versatile surgical routes which show interesting potentials in skull base surgery. Given their “new” trajectory, they can be a very useful adjunct to traditional routes, even being a valid alternative to them in some cases, and add valuable opportunities in selected patients. Indications are constantly expanding, and currently include selected intraorbital, skull base and even intra-axial lesions, both benign and malignant. Given their relatively recent development and thus unfamiliarity among the skull base community, achieving adequate proficiency needs not only a personalized training and knowledge but also, above all, an adequate case volume and a dedicated setting. Current, but mostly future, applications should be selected by genetic, omics and biological features and applied in the context of a truly multidisciplinary environment.